Comparative study of thermostimulated luminescence and electron emission of nitrogen nanoclusters and films - Boltnev, R.E.; Gumenchuk, G.B.; Ponomaryov, A.N.; Savchenko, E.V.; Uyutnov, S.A.; Khyzhniy, I.V.; Lee, D.M.; Khmelenko, V.V.; Pelmenev, A.A.; Krushinskaya, I.N.; Bykhalo, I.B.; Bondybey, V.E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
We have studied thermostimulated luminenscence and electron emission of nitrogen films and nanoclusters containing atomic nitrogen free radicals. Thermostimulated electron emission from N2 nanoclusters was observed for the first time. Thermostimulated luminescence spectra obtained during N2–He sample destruction are similar to those detected from N2 films preirradiated by an electron beam. This similarity reveals common mechanisms of energy transfer and relaxation. The correlation of the luminescence intensity and the electron current in both systems points to the important role of ionic species in relaxation cascades. A sublimation of solid helium shells isolating nitrogen nanoclusters is a trigger for the initiation of thermostimulated luminescence and electron emission in these nitrogen–helium condensates.